2016
DOI: 10.1093/bioinformatics/btw242
|View full text |Cite
|
Sign up to set email alerts
|

WeSME: uncovering mutual exclusivity of cancer drivers and beyond

Abstract: Supplementary data are available at Bioinformatics online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
87
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(90 citation statements)
references
References 37 publications
2
87
0
Order By: Relevance
“…As a cautionary note, TTN and Mucins are very long genes. Yet, the mutual exclusivity pattern of the genes is prominent even after considering the length of the genes, and our previous studies found that the increased mutations in TTN in breast cancer are possibly linked to APOBEC activity [16]. A network based analysis also provided supporting evidence of TTN mutations as a disease marker [27].…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…As a cautionary note, TTN and Mucins are very long genes. Yet, the mutual exclusivity pattern of the genes is prominent even after considering the length of the genes, and our previous studies found that the increased mutations in TTN in breast cancer are possibly linked to APOBEC activity [16]. A network based analysis also provided supporting evidence of TTN mutations as a disease marker [27].…”
Section: Resultsmentioning
confidence: 87%
“…This relation can help identify cancer drivers, cancer-driving pathways, and cancer subtypes [110]. Although less studied, co-occurrence of mutations can also provide critical information about possible synergistic effects between pairs of genes [1113] or underlying mutagenic processes [1416]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the APOBEC mutational signature acts as a footprint of the activity of the APOBEC family of cytidine deaminases. Playing a key factor in many human cancers (Haradhvala et al, 2016;Kanu et al, 2016;Roberts et al, 2013), APOBEC activity has been proposed to be the direct cause of some cancer driving mutations (Burns et al, 2013;Henderson et al, 2014;Kim et al, 2017). As another example, a recent analysis of mutational signatures in the genomes of tobacco smoking-associated cancers provided a novel insight into how smoking increases cancer risk (Alexandrov et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Alexandrov et al 26 characterized dozens of ‘mutation signatures’ defining the nucleotide biases exhibited in subsets of cancers, some with known environmental triggers 27 , others attributable to specific sources of somatic hypermutability 18 , and some of unknown cause. Mechanisms of hypermutability may vary by tumour and over time in ways that are not observed in species evolution 21,2831 . Treatment creates another complication, as chemotherapy or radiation therapy can themselves cause double-strand breaks in the DNA 32 or other forms of hypermutation 33,34 , inducing new mutation signatures 26,30 .…”
mentioning
confidence: 99%